USM PREPARES TO FACE FUTURE CHALLENGES FOR APEX 2020 - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, November 2015 – After achieving many successes throughout 2015 and the previous years, including a handful of academicians acknowledged with various awards such as the National Academic Awards (Anugerah Akademik Negara), Malaysia Rising Star Awards and the Top Research Scientists Malaysia in addition to the impactful expertise of the researchers in the field of archaeology, soil movements, natural disasters, public administration and also in exploring electronic book (ebook) publications at the international level, USM is confident of facing the challenges in the future with greater success.